2016
DOI: 10.1111/acem.13029
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Missed Diagnosis of Ischemic Stroke in the Emergency Department in the Greater Cincinnati/Northern Kentucky Stroke Study

Abstract: Objective Missed diagnoses of acute ischemic stroke (AIS) in the ED may result in lost opportunities to treat AIS. Our objectives were to describe the rate and clinical characteristics of missed AIS in the ED, to determine clinical predictors of missed AIS, and to report tissue plasminogen (tPA) eligibility among those with missed strokes. Methods Among a population of 1.3 million in a five-county region of southwest Ohio and northern Kentucky, cases of AIS that presented to 16 EDs during 2010 were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 19 publications
3
51
1
Order By: Relevance
“…Numerous studies have found that women are more likely than men to report nonfocal symptoms when presenting with acute ischemic stroke 2,3,25 and that the presence of nonfocal symptoms is associated with misdiagnosis. 5, 13,26 We did not find any substantial sex differences in presenting symptoms, but we observed that women and men who reported focal stroke symptoms, with or without accompanying nonfocal symptoms, were at increased risk of having evidence of acute infarct on MRI and were more likely to receive a diagnosis of TIA or stroke. Contrary to the classic teaching that "nonspecific" or "atypical" symptoms are usually associated with stroke mimics, our findings suggested that nonfocal symptoms were common in minor ischemic cerebrovascular events and that these symptoms should not discourage clinicians from pursuing investigations for cerebral ischemia.…”
Section: Discussionmentioning
confidence: 59%
“…Numerous studies have found that women are more likely than men to report nonfocal symptoms when presenting with acute ischemic stroke 2,3,25 and that the presence of nonfocal symptoms is associated with misdiagnosis. 5, 13,26 We did not find any substantial sex differences in presenting symptoms, but we observed that women and men who reported focal stroke symptoms, with or without accompanying nonfocal symptoms, were at increased risk of having evidence of acute infarct on MRI and were more likely to receive a diagnosis of TIA or stroke. Contrary to the classic teaching that "nonspecific" or "atypical" symptoms are usually associated with stroke mimics, our findings suggested that nonfocal symptoms were common in minor ischemic cerebrovascular events and that these symptoms should not discourage clinicians from pursuing investigations for cerebral ischemia.…”
Section: Discussionmentioning
confidence: 59%
“…It is unclear whether an earlier stroke diagnosis in our "missed" cohort would have improved outcome. In the Greater Cincinnati/Northern Kentucky Stroke Study, only 1.1% of patients with a stroke misdiagnosis were eligible for IVT [9]. Not surprisingly, none of our misdiagnosed patients received acute stroke intervention.…”
Section: Discussionmentioning
confidence: 76%
“…Due to the study design, we were also unable to determine whether patient age [9,12] and language discordance were relevant factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the turn of the millennium, the increased availability of MRI and perfusion CT imaging means more cases of minor or transient symptoms can now be recognized to be of ischemic origin. This might be of particular relevance in younger patients, in whom IS is more easily missed initially [ 22 ]. Also, the current, tissue-based definition of a transient ischemic attack (TIA), may have resulted in more cases of transient symptoms to be classified as infarcts as compared to the previous, time-dependent definition [ 21 ].…”
Section: Discussionmentioning
confidence: 99%